Continuous gas-phase hydroformylation of but-1-ene in a membrane reactor by supported liquid-phase (SLP) catalysis. Issue 17 (11th August 2020) - Logemann, Morten; Marinkovic, Jakob Maximilian; Schörner, Markus; José García-Suárez, Eduardo; Hecht, Corinna; Franke, Robert; Wessling, Matthias; Riisager, Anders; Fehrmann, Rasmus; Haumann, Marco
Abstract : The development of a supported liquid phase (SLP) gas-phase hydroformylation catalyst combined with a monolithic membrane separation layer is reported. Abstract : Process intensification is a cornerstone to achieve a significant reduction in energy consumption and CO2 emissions in the chemical industry. In this context, a monolithic membrane reactor combining homogeneous catalytic gas-phase hydroformylation of but-1-ene with in situ product removal is here presented. The homogeneous supported ionic liquid-phase (SILP) catalyst consists of a Rh-biphephos complex dissolved in 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [C2 C1 Im][NTf2 ] and immobilized on a mesoporous silicon carbide monolith. The resulting monolith is catalytically active and selective towards linear aldehyde formation, but the accumulation of aldehyde products and high boilers in the ionic liquid leads to slow catalyst deactivation. This accumulation is suppressed when bis(2, 2, 6, 6-tetramethyl-4-piperidyl)sebacate is used as alternative solvent, where only marginal aldehyde accumulation and aldol formation occur. A polydimethylsiloxane (PDMS) membrane coating of the monolith increases the aldehyde-alkene ratio by an enrichment factor of 2.2 in the permeate gas compared to the retentate gas from the reactor simplifying further downstream processing. The monolithic membrane reactor loaded with SILP or SLP catalysts presents a scalable, versatile platform to achieve process intensification for diverse hydroformylation reactions as well as related gas-phase reactions.